Az emberi erőforrás értékelésének módszertani sajátosságai - Benke, Mariann; Mohácsi, Bernadett (Közép-Európai Közlemények, 2016)
Human capital is the most valuable and expensive resources by a company. It is our organisation’s key strategic asset. Human capital is mainly based on specific knowledge education and special trainings and motivation of employee. Related to last year’s studies in the years 2014 and 2015 this article continues to deal with the valuation opportunities of the human capital. The first part of the study provides a summary about the interconnected nature of the valuation of the human resources. The chapter presents the theory of the human capital based on Gary S. Becker’s microeconomic perspective. The last chapter focuses on the relationship between the value of the human capital and motivation.